(untitled) (Scientific journal of the Fergana State University, 2025)
This article compiles information about the role of geographical factors in the emergence of settlements during historical periods. The geomorphological, climatic, hydrological, and landscape factors influencing urban development are examined using examples from the early settlements in the Fergana Valley. The rhythmic changes of these factors or the reduction of their impact due to industrial development are analyzed through various examples. As a result of industrial progress, the diminishing influence of natural factors on the creation of settlements leads to changes in their territorial distribution, which is substantiated by shifts in the geographical location of ancient settlements in the valley.